2006
DOI: 10.1166/jctn.2006.3058
|View full text |Cite
|
Sign up to set email alerts
|

Optical Absorption Spectra of V+4 Isomers: One Example of First-Principles Theoretical Spectroscopy with Time-Dependent Density Functional Theory

Abstract: The optical absorption spectrum of the three most stable isomers of the Ag11 system was calculated using the time-dependent density functional theory, with the generalized gradient approximation for the exchange and correlation potential, and a relativistic pseudopotential parametrization for the modelling of the ion-electron interaction. The computational scheme is based on a real space code, where the photoabsorption spectrum is calculated by using the formalism developed by Casida. The significantly differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…A method extensively used to calculate the photoabsorption spectrum of nanostructures, surfaces and solids is the time-dependent density functional theory [41,42] (TDDFT), which states a good performance for low electronically correlated systems through the time-evolution of the Kohn-Sham states. Nevertheless, as previously indicated, the implementations used in practice have some well-known limitations due to the approximate description of exchange and correlation effects between the electrons.…”
Section: Excitation Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…A method extensively used to calculate the photoabsorption spectrum of nanostructures, surfaces and solids is the time-dependent density functional theory [41,42] (TDDFT), which states a good performance for low electronically correlated systems through the time-evolution of the Kohn-Sham states. Nevertheless, as previously indicated, the implementations used in practice have some well-known limitations due to the approximate description of exchange and correlation effects between the electrons.…”
Section: Excitation Spectrummentioning
confidence: 99%
“…The finite width of the excitation peaks in an experimental spectrum -linked to the accessible resolution -is mostly determined by the temperature. In our calculations, on the other hand, each excitation peak in the spectrum has been broadened by a Lorentzian profile, where the broadening parameter η is set equal to 0.2 eV, a value commonly used in order to mimic the experimental resolution [42].…”
Section: Excitation Spectramentioning
confidence: 99%
“…In addition, Koponen et al 33 concluded that the LDA performs much better in the TDDFT, compared to static DFT. On the other hand, the most important requirement in obtaining a good photoabsorption spectrum is to have accurate single-particle energies and orbitals, obtained with a good static XC potential, 34,35 while the kernel is less important. The paper by Castro et al 19 presents a discussion of the influence of different XC kernels in the calculation of the optical spectrum of clusters by TDDFT.…”
Section: Excitation Spectrummentioning
confidence: 99%
“…In this equation ⑀ represents the energy, the ⑀ i are the discrete excitation energies obtained by the Casida method, 31,32 and the value of the parameter A determines the full width at half maximum, set in this work equal to 0.05 eV, which is a value commonly used 34 in order to simulate the available resolution in experiments of photoabsorption and photodissociative spectroscopy. This formalism has provided successful results in the calculation of the photoabsorption spectra of atoms, and different types of clusters, [34][35][36][37][38][39] even at high excitation energies. 35 Figure 7 shows the calculated photoabsorption cross sections of the neutral Al n H n+2 and anionic Al n H n+2 − clusters for excitation energies up to 12 eV.…”
Section: Excitation Spectrummentioning
confidence: 99%
“…Time-dependent density functional theory (TDDFT) found wide application in chemistry and applied physics for calculating the electronic excitations of smaller and larger molecules. , This type of calculation has been well-implemented using the polarized continuum model (PCM) to understand the phenomenon of solvatochomism in various organic and organometallic systems. , Hence, relying on the TDDFT method, we have implemented this method to evaluate the ground-state electronic transitions of various alkali metal (Li + , Na + , and K + ) cation−π complexes of benzene and borazine. We have considered cation−π complexes of benzene and borazine having different substituents at 1, 3, 5 position of benzene and at the boron atoms in borazine (Scheme ).…”
Section: Introductionmentioning
confidence: 99%